Public Service Transformation: Innovative Strategies of Ambon City Government Towards Openness and Public Satisfaction - Bahasoan, Aminah (Jurnal Manajemen Pelayanan Publik, 2024)
This research discusses the public service transformation efforts undertaken by the Ambon Government, focusing on innovative strategies aimed at achieving transparency and improving public satisfaction. Using a qualitative approach and case study method, this research explores various aspects of the government's initiatives to innovate public services, involving in-depth interviews, participatory observation, and document analysis to reveal the complexity of the innovative strategies implemented. The results reveal a paradigm shift in service delivery, characterized by the integration of advanced technology, smart governance principles, and citizen-oriented practices. The emphasis on openness is reflected in the utilization of information and communication technologies to disseminate real-time information, policy updates, and detailed procedures. Digital platforms, including online portals and smart apps, significantly improve accessibility, empower citizens with diverse information, and shape a culture of openness. In addition, the government's commitment to citizen participation is emphasized through its involvement in the decision-making process. Participatory forums and feedback mechanisms have facilitated active engagement, ensuring that people's voices contribute to policy formulation and service improvement. The research reflects on how this inclusive approach has positively impacted citizen satisfaction and trust in the government, leading to 34 awards in public service innovation throughout 2023.